1990
DOI: 10.1096/fasebj.4.1.2136839
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and morphologic properties of single muscle fibers in the rat after spaceflight, Cosmos 1887

Abstract: The adaptation of a slow (soleus, Sol) and a fast (medial gastrocnemius, MG) skeletal muscle to spaceflight was studied in five young male rats. The flight period was 12.5 days and the rats were killed approximately 48 h after returning to 1 g. Five other rats that were housed in cages similar to those used by the flight rats were maintained at 1 g for the same period of time to serve as ground-based controls. Fibers were classified as dark or light staining for myosin adenosine triphosphatase (ATPase). On the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 15 publications
1
30
0
Order By: Relevance
“…42,59 Using immunocytochemistry to determine fiber type, the percentage of soleus fibers showing a positive reaction with both slow and fast MHC antibodies increased from 0 to 16% following 14 days of inactivity, whereas those reacting only to slow MHC antibodies declined from 90 to 76%. 63 Thus inactivity increases the number of fibers coexpressing two myosin isoforms in antigravity slow muscles by inducing fast myosin expression in slow fibers.…”
Section: Inactivity and Fiber-type Transformationmentioning
confidence: 99%
“…42,59 Using immunocytochemistry to determine fiber type, the percentage of soleus fibers showing a positive reaction with both slow and fast MHC antibodies increased from 0 to 16% following 14 days of inactivity, whereas those reacting only to slow MHC antibodies declined from 90 to 76%. 63 Thus inactivity increases the number of fibers coexpressing two myosin isoforms in antigravity slow muscles by inducing fast myosin expression in slow fibers.…”
Section: Inactivity and Fiber-type Transformationmentioning
confidence: 99%
“…Atrophy of soleus muscle fibers in response to gravitational unloading by actual spaceflight (Allen et al, 1996;Martin et al, 1988;Miu et al, 1990;Oganov and Potapov, 1976;Ohira et al, 1992;Tischler et al, 1993) or hindlimb suspension (Ohira et al, 1992;Talmadge et al, 1996;Tischler et al, 1993;Winiarski et al, 1987) has been reported in the previous studies. Wang et al (2006) reported fiber atrophy in soleus muscle of Wistar Hannover rats following 16 days of hindlimb unloading (Fig.…”
Section: Fiber Sizementioning
confidence: 62%
“…On the other hand, fiber atrophy is induced during the periods of decreased neuromuscular activity, e.g., in response to gravitational unloading by actual spaceflight (Allen et al, 1996;Martin et al, 1988;Miu et al, 1990;Oganov and Potapov, 1976;Ohira et al, 1992), or simulation models such as hindlimb suspension of rats (Ohira et al, 1992;Talmadge et al, 1996;Tischler et al, 1993;Winiarski et al, 1987) and/or human bedrest (Ohira et al, 1999). Such atrophy is prominent in antigravity muscles, such as soleus, composed of mainly slow-twitch fibers (Goldspink et al, 1986;Ohira et al, 1987 and1992) and with a marked reduction in fiber length and tension development due to plantarflexion of ankle joints during gravitational unloading Ohira et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In skeletal muscle, this large complex of membraneassociated proteins links the sub-sarcolemmal actin cytoskeleton to the extracellular matrix and is thought to provide protection from stresses imposed during muscle contraction (Petrof et al 1993). The increased expression of -DG and -syn in HU muscles parallels the slow-to-fast twitch conversion of soleus Wbers: this phenomenon involves a reduction in slow-type I MHC isoform and an increase in fast IIA MHC, in which soleus muscle gains some fast-twitch mechanical features (Miu et al 1990) but does not increase the force generation. Consequently, the increase in DGC follows the conversion of slow-to-fast twitch Wbers even though there is not a strong increase in contractile activities, and this is probably a reactive mechanism for protecting muscle Wbers.…”
Section: Dgc and Aqp4 Expression After Suspensionmentioning
confidence: 99%